The Impact of Merger Bank Syariah Indonesia Policy on The Work Ethic at BSI Megamas Boulevard Manado - Samad, Telsy; Muttaqin, Zein (Al-Mashrafiyah: Jurnal Ekonomi, Keuangan, dan Perbankan Syariah, 2022)
The Indonesian Sharia Bank merger policy is a major momentum in the development of Islamic banking and finance in Indonesia. This study aimed to determine the impact of the merger policy of Bank Syariah Indonesia on work ethic. By using qualitative research methods, this study seeks to carefully describe the impact of the merger of Bank Syariah Indonesia on the work ethic of BSI employees in the Megamas Boulevard area of ​​Manado. The findings of this study reveal that BSI’s merger policy has a positive impact on several aspects of the 6 out of 8 professional work ethos mentioned by Johnson, Mr. Ethos in Indonesia, namely in the aspect of Work is Trust, Work is Actualization, Work is Art, Work is Honor, Work is a Call, and Work is Service. This certainly indicates that the merger policy carried out by BSI has resulted in increased interest, enthusiasm, and work ethic among employees at BSI Megamas Boulevard Manado. The other 2 ethos, namely Work is Grace and Work is Worship, did not significantly impact changes related to the work ethic of BSI employees. So it can be concluded that the overall merger policy of Bank Syariah Indonesia has a positive impact on the work ethic of BSI employees in Megamas Boulevard Manado.